Epitaxial growth of complex oxides on semiconductors - Posadas, Agham-Bayan S. (Yale University, 2007)
In combining two dissimilar materials in an epitaxial heterostructure, there are several major considerations that one must take into account in order to be successful. In this thesis, we study the integration of semiconductors with complex oxides. As demonstrations of how one should think about the epitaxial growth of complex oxides on semiconductors, we study two materials systems that highlight the major concerns that need to be addressed.